Cephalic vs. subclavian lead implantation in cardiac implantable electronic devices: a systematic review and meta-analysis. Issue 1 (17th July 2018) - Benz, Alexander P; Vamos, Mate; Erath, Julia W; Hohnloser, Stefan H
Abstract: Aims: Cephalic vein cutdown (CVC) and subclavian puncture (SP) are widely used techniques for lead insertion of cardiac implantable electronic devices (CIEDs). Whether one technique is superior to the other, is still being debated. The purpose of this study was to compare CVC vs. SP for lead implantation in CIEDs with respect to the incidence of pneumothorax, lead failure, and bleeding. Methods and results: We performed a systematic search of the pertinent literature on lead implantation in CIEDs via PubMed and Cochrane databases published over the last 25 years. Standard meta-analytic methods were applied to compare incidences of outcomes of interest. Sensitivity analysis was conducted to determine the impact of each study on the overall effect size. Risk of publication bias was assessed. A total of 20 studies were included in the analysis. These studies comprised more than 30 000 patients with more than 50 000 leads implanted via CVC or SP. The incidence of pneumothorax was lower with the CVC technique ( n  = 29/15 065, 0.19% vs. n  = 205/15 824, 1.30%) [odds ratio (OR) 0.21, 95% confidence interval (CI) 0.10–0.42, P  < 0.001]. With respect to overall lead failure, CVC was associated with better outcomes as compared to SP ( n  = 10/2002, 0.50% vs. n  = 40/2080, 1.92%) (OR 0.25, 95% CI 0.13–0.51, P  < 0.001). There was no significant difference in bleeding events ( n  = 25/811, 3.08% vs. n  = 20/2136, 0.94%) (OR 1.69, 95% CI 0.37–7.79, P  = 0.50). Conclusion: This comprehensive meta-analysis demonstrates lower risk for pneumothorax and lead failure associated with CVC as compared to SP. Cephalic vein cutdown should constitute the preferred venous access.